Local-level appraisal of benefits and barriers affecting adoption of climate-smart agricultural practices: Ghana - Peterson, C.A. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
Although Climate-Smart Agricultural (CSA) practices are expected to boost adaptive capacity, food security and climate change mitigation in resource poor, smallholder farming systems, the barriers that can restrict their uptake are diverse. This study investigated the principal barriers hindering the adoption of CSA practices in the Upper West region of Ghana with the aim of inventorying existing uptake of CSA and providing recommendations to CCAFS as to practices with potential for further research or implementation on the farm level. A questionnaire survey of 60 households in 2 villages in Lawra District, in addition to focus group discussions and semi-structured interviews, revealed that non-adoption was most often a result of insufficient financial capital, difficult access to or low availability of the necessary agricultural inputs (tools, seeds and fertilizers), water scarcity, and in some cases insufficient labor to carry out the practice. Women farmers were often less aware of CSA practices than men and were more likely to perceive increased labor load as a disadvantage to adopting them. The author noted rainwater harvesting, improved crop varieties, efficient fertilizer use, and improved forages, as well as continued use of pit composting, as practices with high potential for further CCAFS investigation and/or on-farm participatory trials.